(Mal)Adaptation opportunism: when other interests take over stated or intended climate change adaptation objectives (and their unintended effects). Issue 9 (2nd September 2018) - Owusu-Daaku, Kwame N.
ABSTRACT: This paper introduces the terminology of (mal)adaptation opportunism – a situation in which projects undertaken in the name of climate change adaptation (CCA) are overrun by interests other than the stated or intended objectives of the CCA project. A goal of CCA projects is to reduce poverty and promote social justice. The case of the threat of displacement of the community of Kewunor by the Trasacco Estate Development Company (TEDC), after the construction of the Ada Sea Defense System (AdSDS) of Ghana as a CCA, is illustrative of this concept of (mal)adaptation opportunism. Through a narrative presentation of eight different accounts concerning this issue, I demonstrate how (mal)adaptation opportunism arises and is often motivated by economic interests. This case illustrates how economic interests can take over not only CCA projects but also their maladaptive effects.